Collaboration business intelligence prototype for the synergy of empowering MSMEs in the government agencies - Maryadi, Maryadi; Asqolani, Asqolani; Sopian, Sopian (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
Purpose – This research develops a business intelligence prototype based on the analysis of profile data, problems, and needs of MSMEs.Design/methodology/approach – This research uses the descriptive analysis method by collecting data through interviews and documentation.Findings – Based on a sample of 5 respondent technical units in the Ministry of Finance, this research develops a prototype to empowering MSMEs in business sectors, problems, and needs of MSMEs that are fostered by several technical units in a government agency can be integrated and presented in business intelligence. This analytical tool can be used jointly by technical units to make decisions in preparing MSME empowerment programs.Research limitations/implications – The business intelligence model has just been developed based on data and discussions from 3-5 technical units in the Ministry of Finance and does not yet reflect the data and information needs of the Ministry of Finance as a whole. Practical implications – Government institutions that have not yet implemented business intelligence that supports MSME empowerment activities can develop this prototype into a fully functional system and can be used for synergistic empowerment of MSMEs.Originality/value – This research is intended to complement the limited discussion regarding the application of business intelligence in government institutions.